How to sell your home without a broker - Carey, Bill (J. Wiley, 2004)
With the high commissions being charged in today's housing market and the convenience of the Internet as a selling tool, many Americans find it more affordable to sell their own homes. This new edition of the indispensable home seller's how-to guide can save you thousands of dollars in real estate fees and commissions by showing you how to successfully market, negotiate, close, and wrap up the sale of your home-without paying a broker's high fees.